2016
DOI: 10.1016/j.soildyn.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Closed form solution of Eigen frequency of monopile supported offshore wind turbines in deeper waters incorporating stiffness of substructure and SSI

Abstract: Offshore wind turbines (OWTs) are dynamically loaded structures and therefore the estimation of the natural frequency is an important design calculation to avoid resonance and resonance related effects (such as fatigue). Monopiles are currently the most used foundation type and are also being considered in deeper waters (>30 m) where a stiff transition piece will join the monopile and the tapered tall tower. While rather computationally expensive, high fidelity finite element analysis can be carried to find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 28 publications
4
74
0
20
Order By: Relevance
“…Arany et al (2016)), it is suggested that the best approach to estimate the foundation stiffness is the methods of Poulos and Davis (1980) and Randolph (1981). Furthermore, in the authors' experience the slender pile formulae give stiffness results that produce better approximations of the Eigen frequency of the structure than the formulae for stocky (rigid) piles.…”
Section: Foundation Stiffness Of Monopilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Arany et al (2016)), it is suggested that the best approach to estimate the foundation stiffness is the methods of Poulos and Davis (1980) and Randolph (1981). Furthermore, in the authors' experience the slender pile formulae give stiffness results that produce better approximations of the Eigen frequency of the structure than the formulae for stocky (rigid) piles.…”
Section: Foundation Stiffness Of Monopilesmentioning
confidence: 99%
“…The natural frequency is calculated following Arany et al (2015a) and Arany et al (2016), as shown in Section 2.6. The first natural frequency and the damping of the first mode in the along-wind and cross-wind directions are used to obtain the dynamic amplification factors (DAF) that affect the structural response.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the frequency of this loading is extremely low and is in the order of magnitude of 100s (see Figure 1). Typical period of wind turbine structures being in the range of about 3 seconds [22] no resonance of structure due to wind turbulence is expected resulting in cyclic soil-structure interaction. On the other hand, the wave loading will also apply overturning moment at the mudline and the magnitude depends on water depth, significant wave height and peak wave period.…”
Section: Figure 1: Loads Acting On a Typical Offshore Wind Turbine Fomentioning
confidence: 99%
“…The wave loading can be mildly dynamic or severely dynamic depending on the turbine size. The interactions of these loads could be complicated (Arany et al, 2016), but they are not considered in this paper. The typical excitation ranges are 1P (0·18$0·32 Hz) and 3P (0·5$1 Hz).…”
Section: Comparison With Centrifuge Testing Resultsmentioning
confidence: 99%